ENHANCING ENGINEERING INFRASTRUCTURE IN RESIDENTIAL BUILDINGS FOR IMPROVED LIVING STANDARDS - Saydullaev, Sirojiddin; Kuychiyev , Utkir; Kurbanbayev , Sarvar (Educational Research in Universal Sciences, 2023)
Elevating living standards in residential buildings entails a comprehensive approach to engineering infrastructure. This article outlines key methodologies aimed at enhancing infrastructure within residential spaces to improve comfort, sustainability, and overall quality of life for occupants. The strategies discussed encompass innovative approaches to electrical systems, water supply, HVAC (heating, ventilation, and air conditioning), waste management, and digital connectivity. Understanding and implementing these approaches collectively serve as a foundation for creating more efficient, sustainable, and comfortable living environments within residential structures.